ANALYSIS OF DISMISSAL OF BANKRUPT NOTARY POSITIONS BASED ON NOTARY OFFICE LAW AND BANKRUPTCY LAW - Aulia Raihan; Selamat Widodo (JOURNAL EQUITABLE, 2024)
Many people believe that it cannot be justified to dismiss a Notary dishonorably just for reasons of bankruptcy, as determined by the Court. If we look closely of Article 12 letter a of the Law on the Position of Notaries, it turns out that the meaning of this article is unclear. It is not clear whether the Notary was bankrupted in his personal capacity as an individual (natuurlijk person) or in his official function as a public official. The issues that will be discussed are the procedures for terminating the position of a bankrupt notary and whether the dismissal of the notary's position is in accordance with the principles of justice. The research methodology used is normative juridical research. The findings of this research indicate that a Notary who is declared bankrupt can be temporarily dismissed from his position as intended in Article 9 paragraph (1) letter a. Furthermore, if the bankruptcy statement has permanent legal force, the Notary can be permanently dismissed from his position by the Minister, on the recommendation of the Supervisory Board of the Central Supervisory Board, as intended in Article 12 letter a of Law Number 2 of 2014 concerning the Position of Notaries. The Bankruptcy Law does not explicitly regulate the role of Notaries. However, it can be concluded that persons subject to the regulations outlined in the Bankruptcy Law are limited to legal incompetence and are not permitted to exercise control over their assets.